DOWNWARD ACCOUNTABILITY TO IMPROVE MALAYSIAN NONPROFIT ORGANISATIONS - Nurul Hidayana Mohd Noor; Saunah Zainon; Hasnatulsyakhira Abdullah Hadi; Ahmad Naqiyuddin Bakar (Journal of Islamic, Social, Economics and Development, 2023)
Nowadays, the role of NPOs has become more critical since several unfortunate events, such as the outbreak of the pandemic and the natural disasters that frequently happened. NPOs act as helping hands for the government to handle public affairs, making them accountable to the public. Their stakeholders demand their effectiveness in performing their primary duty: serving their beneficiaries. Hence, accountability mechanisms must be implemented within NPOs. It can be achieved through information disclosure and feedback, and complaint procedures. This study determined the relationship between accountability mechanisms and NPOs effectiveness. Previous studies have found that accountability mechanisms, information disclosure, and feedback and complaint procedure have a positive relationship with NPOs effectiveness. In addition, this research focused on the context of Malaysian welfare NPOs. For the methodology, this research applied a quantitative research design and used a questionnaire survey that involved 40 staff of welfare NPOs located in Klang Valley. Therefore, this research will improve the accountability practice in Malaysian NPOs to level up their effectiveness in serving their beneficiaries in the future and meet the satisfaction of other stakeholders